A study on fire safety at private religious colleges (hostel building) / Rahimi Izzat Roslan - Roslan, Rahimi Izzat (Faculty of Architecture, Planning and Surveying, 2008)
The private religious collages usually lack in a fire safety. It not have enough budget because of limited funding, that no helped form government. The aim of this research is to study the about fire safety provided at schools hostel building. The hostel is uses for situated student This study is carried out on the following three objectives which includes; to identify about fire safety provided in the private school hostel, to study the efficiency of the system implemented to Private Religious School, and to get feedback from occupant to detect the problem happen on fire safety in hostel. A total of sixty questionnaires were distributed to Sekolah Agama Menengah Tinggi Tengku Ampuan Jemaah, Sekolah Agama Menengah Bestari Jais, and Sekolah Agama Kafa Integrasi that located in Selangor area. Fifty one questionnaires were returned completed out of sixty questionnaires that were distributed. The respondents were teacher, staff and student. The interview session between school management are made to know the condition fire safety at hostel building and during distribute questionnaire, the observation to the fire safety provided. From the analysis it was found that the fire safety provided is not enough provided base on guidelines by Fire and Rescue Department Malaysia. The supervision by school management is lack, not inspection and maintenance work done to fire safety or less. From the respondents result, they not satisfy with fire safety provided. The most effective way to educate the users from the survey is through campaigning in mass media but only the general knowledge is addressed, however fire safety training cannot be neglected as it is perceived by the respondents as not effective since it provides the crucial training and information on fire safety.